Consequences of crisis in Tunisia: transformatioin of economic system - S. Yu. Babenkova (Путеводитель предпринимателя)
Diversified economy of Tunisia of the beginning of the XXI century can be one of the most successful examples of operation of the government in North African countries, but before the events of 2011 it faced a lot of such problems as slow economic growth, high rate of inflation, unemployment and expansion of the sector of shadow economy. It must be noted that since the 1960s the economy of the country was directed to the strengthening of export items of income and the growth of foreign investments and revenues from tourism. The main exports included goods of light and food industry, oil products, chemicals and phosphate. About 80% of export accounted for European Union countries. This export-oriented policy of the country together with investment programmes to support the education had its positive effect: growth of GDP by 4-5% a year, increase in the standard of living and quality of life. Despite the fact that ex-president of the country Zine El Abidine Ben Ali continued this policy, his reign was marked by the growth of corruption among the public officials, the increase in unemployment among university graduates. His toppling in 2011 in the result of the coup d’etat undermined the economy of Tunisia, in the part of the reduction of foreign investments and revenues from tourism. Currently the country government in conjunction with the Central Bank of Tunisia are taking a number of actions in the social and economic, and financial areas. The looming liquidity crisis, the unemployment level incessant after the events of 2011, terrorist attacks aimed at the tourist sector, workers’ strikes in the phosphate sector, delayed GDP growth in the period of2015-2017 by nearly 15% which is a negative trend in the post-revolutionary development of the country.